Lean approach in the agrifood chain: a systematic bibliographic review - Cuer, Laiane [UNESP]; Correa Bernardo, Cristiane Hengler [UNESP]; Scalco, Andrea Rossi [UNESP] (Univ Nove Julho, 2019)
Agribusiness plays a prominent role in the Brazilian economy. Its performance involves the displacement of raw materials and finished products to the final consumer, which is accomplished through the supply channels. Throughout the supply chain, waste can occur. In the industrial environment lean is very used to minimize this problem. In this way several agrifood chains have sought techniques adopted in manufacturing to solve and manage their processes, such as lean. This research seeks, in general terms, to identify through a systematic bibliographic review (RBS) in the main databases of scientific journals that focuses on the application of the Lean Production methodology in agrifood chains, in order to analyze the breadth of the work in terms tools for its application and the contributions of these studies. The articles selected in RBS also note the need to integrate lean deployment into all links in the chain for better effectiveness. It was observed that the most used tools in the publications regarding the application of lean in the agrifood chain were Value Stream Mapping (VSM), Quality Function Deployment (QFD) and Food Value Chain Analysis (FVCA). With more lean application in the supply chain of the red meat segment. The articles mention that achieving lean positive results in supply chains is important for a lean deployment integration to occur at all links in the chain. Most studies of lean applications occurred in the UK following a government incentive. There were no studies of lean implantation in the agro-food sector whose application was in Brazil.
Keywords: Supply Chain; Agri-Food Supply Chain; Agribusiness; Systematic Bibliographic Review; Lean